Management Strategies for POSEIDON Groups 3 and 4 - Haahr, Thor; Dosouto, Carlos; Alviggi, Carlo; Esteves, Sandro C.; Humaidan, Peter (Frontiers in Endocrinology, 2019)
In the POSEIDON classification patients belonging to groups 3 and 4 share the same common feature of a poor ovarian reserve independently of age, rendering them at high risk of a poor reproductive outcome. Overall, POSEIDON groups 1-4 constitute approximately 47% of patients attending assisted reproductive technology (ART) treatment. With the increasing delay in childbearing, POSEIDON group 4 seems to increase in numbers now in some centers constituting more than 50% of the total POSEIDON population, whereas group 3 patients constitute approximately 10%. Both POSEIDON groups 3 and 4 patients require special attention as regards pretreatment strategy, ovarian stimulation, adjuvant treatment and ovulation trigger strategy in order to optimize the probability of having at least one euploid blastocyst for transfer. Although more evidence is needed, recent advances within the field seem to have increased the reproductive outcomes in the low prognosis patient. The key to success is individualization in all steps of ART treatment. Herein, we review the recent evidence for the management of POSEIDON groups 3 and 4.